Effect of Neutropenic Diet on Infection Rates in Cancer Patients With Neutropenia: A Meta-analysis of Randomized Controlled Trials. (March 2019) - Ball, Somedeb; Brown, Timothy J.; Das, Avash; Khera, Rohan; Khanna, Sahil; Gupta, Arjun
Abstract : Introduction: Neutropenic diets are commonly prescribed to cancer patients with neutropenia with the intention of reducing rates of infection. These diets are restrictive and are associated with lower patient satisfaction and possibly malnutrition. Further, it is unclear if these restrictive diets are effective in reducing infection. We performed a meta-analysis on the rates of infection reported in trials comparing the neutropenic diet to unrestricted diets in cancer patients with neutropenia. Methods and Materials: A comprehensive database search for all published randomized controlled trials comparing infection rates in cancer patients receiving a neutropenic diet versus an unrestricted diet was performed for all publications in English language from database's inception until September 12, 2017. The search strategy, study selection, and subsequent analysis adhered to PRISMA guidelines. Random effects modeling was used to obtain pooled relative risks. The primary outcome measure was the rate of infection. Results: Five randomized controlled trials with a total of 388 patients were included in the final analysis. Patients mostly had acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), or sarcoma. Infection was noted in 53.7% patients in the neutropenic diet group, as compared with 50% in the unrestricted diet group. No significant difference in infection rate was observed between the neutropenic diet versus unrestricted diet groups, pooled risk ratio (RR) 1.13 (95% CI, 0.98-1.30; P =0.10). Conclusions: This meta-analysis of randomized controlled trials suggests that the use of neutropenic diet was not associated with decreased risk of infection in neutropenic cancer patients. The continued use of neutropenic diets should be questioned. Abstract : Supplemental Digital Content is available in the text.